APPLICABILITY OF CHAPRA’S MODEL OF ISLAMIC BANKING IN NIGERIA - O., Yaqub J.; T., Bello H. (European Scientific Journal, ESJ, 2012)
The banking sector occupies a vital position in the economy and must be subject to continuous reforms for it to function efficiently. It is in this direction that, the introduction of Islamic banking by the Central Bank of Nigeria (CBN) is expected to usher in ethical financing with great benefits to entrepreneurs especially small and medium scale. However, there are two main contending models of Islamic banking. Therefore, this study attempts descriptive and analytical expositions of the two models and suggest the appropriate model for Nigeria which is not an Islamic State.